2020
DOI: 10.1101/2020.11.13.379719
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

O mouse, where art thou? The Mouse Position Surveillance System (MoPSS) - an RFID based tracking system

Abstract: Existing methods for analysis of home cage based preference tests are either time consuming, not suitable for group management, expensive and/or based on proprietary equipment that is not freely available. For this reason, we developed an automated system for group housed mice based on radio frequency identification: the Mouse Position Surveillance System (MoPSS). The system uses an Arduino microcontroller with compatible components, it is affordable and easy to rebuild for every laboratory. The MoPSS was vali… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 34 publications
(112 reference statements)
0
10
0
Order By: Relevance
“…The mouse tag detections were automatically saved onto a microSD card during the experiment and each detection was marked by a current timestamp with the antenna number (left/right) and the individual mouse RFID tag number. Data analysis and sanity checks with logical correction of missing detections were done using a data evaluation script in the software R (R version 4.0.4, R Studio version 1.3.959) specially developed for MoPSS data analysis 29 . Stay times for each of the twelve mice in each cage side were calculated as times between cage changes when a mouse tag was detected at a new cage.…”
Section: Analysis Of Preferencementioning
confidence: 99%
See 4 more Smart Citations
“…The mouse tag detections were automatically saved onto a microSD card during the experiment and each detection was marked by a current timestamp with the antenna number (left/right) and the individual mouse RFID tag number. Data analysis and sanity checks with logical correction of missing detections were done using a data evaluation script in the software R (R version 4.0.4, R Studio version 1.3.959) specially developed for MoPSS data analysis 29 . Stay times for each of the twelve mice in each cage side were calculated as times between cage changes when a mouse tag was detected at a new cage.…”
Section: Analysis Of Preferencementioning
confidence: 99%
“…Stay times for each of the twelve mice in each cage side were calculated as times between cage changes when a mouse tag was detected at a new cage. It has been shown that the time spent in the tube is neglectable for preference calculation 29 and therefore we did not subtract the time spent in the passaging tube. Stay durations over the 46 hours testing period of each single experiment were summed up for each mouse and then calculated as percentage of the total time.…”
Section: Analysis Of Preferencementioning
confidence: 99%
See 3 more Smart Citations